Analysis of Critical Thinking of IPS Education Students - Syamsiar, Huldiya; Kerti Nitiasih, Putu; Nanci Riastini, Putu (KnE Social Sciences, 2024)
Critical thinking is the skill to objectively analyze, evaluate, and solve problems using logical and rational thinking. Critical thinking skills are useful in many aspects of life, including making effective decisions and evaluating arguments. Students’ critical thinking skills refer to students’ skills to actively analyze, evaluate, and solve problems rationally. The purpose of this research is to know the analysis of critical thinking skills in IPS education programs. This literature review study used the systematic literature review (SLR) method. The analysis showed that there is variation in the level of critical thinking ability among social studies students. Some students may demonstrate higher abilities in analyzing, evaluating, and relating social studies-related information, while others may still need to improve their critical thinking skills. The need for improvement in the critical thinking skills of social studies education students; and the need for an increase in learning approaches that focus on the development of critical thinking. Teachers can integrate teaching strategies that stimulate analytical thinking. Keywords: skills analysis, critical thinking, social studies education